THE EFFECT OF USING WEBTOON COMICS IN READING COMPREHENSION OF SEVENTH-GRADE STUDENTS AT SMPN 3 BANYUWANGI IN THE ACADEMIC YEAR 2023/2024 - Wulan Elok Wahyu Lestari; Nur Hasibin; Inayah, Arin; Abdul Halim (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2025)
The purpose of this research was to find out whether using Webtoon Comics has an effect on reading comprehension of procedure text. This research used a quantitative research method with a one-group pre-test and post-test pre-experimental research design. The respondents were 34 students in seventh grade. The researcher gave the students a pre-test before giving the treatment, and the post-test was given after the students received treatment from the researcher. In this research, the data was collected by giving a test. The T-test analysis formula was used in this research to determine the difference between the average of the post-test and the pre-test in the experimental class. The T-test was analyzed and interpreted with the degree of signification level was 5% with df = 33, and the t-table was 2.034. The result of the T-test analysis was 10.092. It means that the T-test (10.092) was higher than the t-table (2.034) in the significance of 5%. Based on the research results, it can be concluded that the use of Webtoon Comics as learning media was effective for learning reading comprehension